2019
DOI: 10.1007/s00394-019-02101-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute p-synephrine ingestion increases whole-body fat oxidation during 1-h of cycling at Fatmax

Abstract: Purpose: p-Synephrine, the principal alkaloid of bitter orange (Citrus aurantium), is widely used in dietary supplements for weight loss due to its purported effect of increasing fat oxidation. However, there is a paucity of scientific information about its effectiveness in enhancing fat oxidation during exercise. The aim of this investigation was to determine the effect of an acute dose of p-synephrine on substrate oxidation during prolonged and constant intensity exercise. Methods: In a double-blind and rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 15 publications
(27 reference statements)
3
35
2
Order By: Relevance
“…As a result, it seems safe to indicate that p-synephrine is effective to enhance fat utilization during exercise of low to moderate intensity. In fact, it has been recently found that 3 mg/kg of body mass of p-synephrine increased the amount of fat oxidized during 1 h of exercise at Fatmax, equivalent to~57% VO 2max from 33.6 to 37.3 ± 9.8 g [32]. Interestingly, the co-ingestion of p-synephrine and caffeine does not produce a synergistic effect on fat oxidation during exercise over the benefit of these substances when they are ingested isolatedly [33].…”
Section: Effect Of P-synephrine To Shifting Substrate Oxidation During Exercisementioning
confidence: 97%
See 4 more Smart Citations
“…As a result, it seems safe to indicate that p-synephrine is effective to enhance fat utilization during exercise of low to moderate intensity. In fact, it has been recently found that 3 mg/kg of body mass of p-synephrine increased the amount of fat oxidized during 1 h of exercise at Fatmax, equivalent to~57% VO 2max from 33.6 to 37.3 ± 9.8 g [32]. Interestingly, the co-ingestion of p-synephrine and caffeine does not produce a synergistic effect on fat oxidation during exercise over the benefit of these substances when they are ingested isolatedly [33].…”
Section: Effect Of P-synephrine To Shifting Substrate Oxidation During Exercisementioning
confidence: 97%
“…In all the abovementioned investigations, the increases in fat oxidation rate with p-synephrine were accompanied by a concomitant reduction in carbohydrate oxidation rates [28,[30][31][32]. This is because p-synephrine does not modify energy expenditure rates at any exercise intensity, which contradicts its potential thermogenic effect, at least during exercise.…”
Section: Effect Of P-synephrine To Shifting Substrate Oxidation During Exercisementioning
confidence: 97%
See 3 more Smart Citations